2012
DOI: 10.4103/1319-3767.98426
|View full text |Cite
|
Sign up to set email alerts
|

Results of short- and long-segment cardioesophageal myotomy for achalasia

Abstract: Background/Aim:We report the results of a short- and long-segment cardiomyotomy for relief of the symptoms of achalasia.Patients and Methods:From 1997 to 2009, 41 patients (22 men, 19 women) with achalasia underwent cardiomyotomy. Patients were divided into 2 groups [short-segment group (SSG) and long-segment group (LSG)]. SSG include 22 patients with laparotomy and 8-cm short-segment myotomy and Dor fundoplication. LSG includes 19 patients with thoracotomy and 12-cm long-segment myotomy and Belsey partial fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…16 The gastric myotomy is not an easy step of the operation as the muscle layers are ill defined and the submucosal plane is poorly cleared, submucosal gastric vessels are easily divided, bleed and masking the field by bleeding, and the mucosa is delicate and thin. [16][17][18][19][20] Incidence of perforation of the esophageal mucosa was higher in the group with myotomy <1.5 cm, whereas incidence of perforation of the gastric mucosa was higher in the group with myotomy 1.5 to 2.5 cm. However, this difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…16 The gastric myotomy is not an easy step of the operation as the muscle layers are ill defined and the submucosal plane is poorly cleared, submucosal gastric vessels are easily divided, bleed and masking the field by bleeding, and the mucosa is delicate and thin. [16][17][18][19][20] Incidence of perforation of the esophageal mucosa was higher in the group with myotomy <1.5 cm, whereas incidence of perforation of the gastric mucosa was higher in the group with myotomy 1.5 to 2.5 cm. However, this difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 90%
“…Some authors tried to minimize it in order to safeguard part of the lower esophageal sphincter expecting that protect against GERD. [17][18][19][20] Other authors adopted more extension of the myotomy ( > 2 to 3 cm) on the gastric side to achieve much better ablation to the LES and achieve better elimination of dysphagia. 4,21,22 Oelschlager et al 14 reported that extended myotomy on the gastric side of 3 cm more efficiently divides the LES than 1.5 cm myotomy, thus improving the surgical outcomes of LHM in terms of improvement of dysphagia without development of abnormal GERD provided that a Toupet fundoplication is performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation